As (im)possíveis relações entre a capoeira capixaba e o candomblé (Ágora Journal, 2020)
Capoeira and Candomblé are manifestations developed in Brazil,  marked by African ancestry, and influenced by many cultural contacts. As a result of these shared influences, many people mistake the two and see a strong connection between them. In this context, the study aims to identify and analyze the (im)possible socio-cultural relations between Capoeira and Candomblé in capoeira groups in Vitória - ES. Drawing from participant observation, formal and informal semi-structured interviews, and analysis of the literature, it became evident that, in “capoeira capixaba,” there is a certain distance between the elements of these manifestations, through efforts, in different degrees, of the observed groups themselves, who seek to reach slices of a market dominated by the middle class that does not yet identify much with African ethnic elements. These distances are shown in invented traditions that configure their own identity for the capoeira of Grande Vitória, even if with strong influences from Rio de Janeiro and Bahia. Key-words: Capoeira. Candomblé. Relations.